If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7w + -4) + -1(w + 3) = 0 Reorder the terms: (-4 + 7w) + -1(w + 3) = 0 Remove parenthesis around (-4 + 7w) -4 + 7w + -1(w + 3) = 0 Reorder the terms: -4 + 7w + -1(3 + w) = 0 -4 + 7w + (3 * -1 + w * -1) = 0 -4 + 7w + (-3 + -1w) = 0 Reorder the terms: -4 + -3 + 7w + -1w = 0 Combine like terms: -4 + -3 = -7 -7 + 7w + -1w = 0 Combine like terms: 7w + -1w = 6w -7 + 6w = 0 Solving -7 + 6w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6w = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 6w = 0 + 7 6w = 0 + 7 Combine like terms: 0 + 7 = 7 6w = 7 Divide each side by '6'. w = 1.166666667 Simplifying w = 1.166666667
| 3y+5=5y-3y | | -(1-0)3= | | X^2+15-16=0 | | 2(18+-6y)-3y=-24 | | 5n+8=-(2-6n)+8 | | 3xsquared=6-9x | | 8x+12+9(2x-4)= | | 5z-0.6=6z | | -3=a(3-0)-4 | | -3u-1/3u=1/4-7/3 | | (8n-1)+(4n+5)= | | 7y(4y-2)= | | -4ac-5b= | | 2lnx-6=12 | | 3x-20x-7=0 | | x-9+x+5x=180 | | 3=a(3-0)-4 | | -2(7x-4)+6(5x+1)= | | 7x-1-9x+5= | | 4(6x-4)+5(15-3x)-4(2x+3)=-2 | | (x+3)+2x+x=23 | | 3x*3x*3x+4=31 | | 4b+-2a-c= | | 7x-1+9x+5= | | 2j-3=47 | | -18z+6=27z-20 | | y=x^2-10x+106 | | 1+3(m-8)=7-5(6m+6) | | 4+r=6r-3-6r | | 2/5(1-5)x=1/2(4x+3) | | x+1+x+2=180 | | 51-2(11y-12y)= |